PIXTON AS A TOOL FOR PROMOTING HEALTH AND ORAL HYGIENE - Neves de Souza, Kathianna; Neves de Souza Bibiano, Raquel; William Neves Lacerda, Kevin (Health and Society, 2023)
The purpose of this work is to discuss how the use of Pixton software can contribute to the teaching-learning process about the importance of care related to health promotion and oral hygiene care. The aforementioned work proposal presented is based on the construction of dialogues involving comic books on the theme presented in the aforementioned article using the Pixton software, as an important alternative for enriching and improving teaching practices based on the creation of Comics (Comic Books), given that one of the many problems addressed in schools is how to arouse student interest in learning, and this fact can cause several learning difficulties and low academic performance. In order to meet the objectives contained in this proposal, this work has a qualitative research approach in a descriptive format. In an attempt to provide greater clarity on the conceptual aspects, initially, a bibliographical survey was carried out in an attempt to delve deeper and obtain broad knowledge on the topic covered in this work. Based on the information obtained through the research, the results pointed to a reality that is increasingly present in everyday school life, which is, precisely, the need to use methodologies and actions that can make use of some form of technology. We realized that, using the Pixton software, students will be able to create comics and carry out dialogues on various topics related to health and oral hygiene, where they can also present their creativity while carrying out the activities proposed during classes.